"A dangerous tool in the wrong hands": Sovereign technologies in Alanis Obomsawin's Is the Crown at War with Us? and Barry Barclay's The Kaipara Affair. Issue 4 (4th July 2022) - Saggar, Shelley Angelie
ABSTRACT: Abenaki film-maker Alanis Obomsawin's 2002 film Is the Crown at War with Us? and Ngāti Apa film-maker Barry Barclay's 2005 documentary The Kaipara Affair depict tensions between Indigenous sovereignty and global capitalism through the lens of two distinct fishing rights struggles drawn from Canada and Aotearoa/New Zealand. This article examines themes of documentation, surveillance, and environmental resource extraction that echo across both films to argue that these technologies – as narrativized in Obomsawin's and Barclay's works – offer the potential for negotiation in a continuing anti-colonial resistance, both in the localized struggles of Esgenoopetitj/Burnt Church in Canada and Tinopai in Aotearoa/New Zealand, and further suggest potential strategies for emulation across the (post)colonial globe. Andrew Woolford's metaphor of the settler-colonial "net" is used to analyse the depiction of fishing practices as a contested arena for global capitalism and Indigenous stewardship that is narratively and aesthetically challenged by both film-makers.